The Peran Pengetahuan dan Sikap dalam Membentuk Perilaku Pelaporan Insiden Keamanan di Perbankan Mobile - Pandia, Henry (TeIKa, 2024)
The growing reliance on mobile banking has brought convenience to users but also heightened security risks, making the analysis of users' knowledge, attitudes, and behaviors toward information security incident reporting critical. This study investigates these dimensions within the context of mobile banking in Indonesia, aiming to bridge gaps between awareness and action. A survey involving 430 respondents was conducted, utilizing an instrument adapted from the Human Aspect of Information Security Questionnaire (HAIS-Q). Statistical analyses, including Cronbach's alpha, composite reliability, and Average Variance Extracted (AVE), were employed to validate the constructs. The results reveal that while respondents exhibit high levels of knowledge (mean = 4.21) and positive attitudes (mean = 4.20), their proactive reporting behaviors are relatively low (mean = 3.26). Path coefficient analysis indicates that knowledge strongly influences attitudes (0.722) but has a weaker direct impact on behaviors (0.162). Gender differences also play a significant role, affecting knowledge and behavior. These findings underscore the need for targeted interventions, including enhanced training, supportive reporting cultures, and robust monitoring mechanisms, to mitigate risks and improve incident reporting practices. Future research should explore psychological and technological factors to further enhance mobile banking security.